The Influence of Individual and Situational Factors on Teachers’ Justice Ratings of Classroom Interactions - Kobs, Scarlett; Ehlert, Antje; Lenkeit, Jenny; Hartmann, Anne; Spörer, Nadine; Knigge, Michel (Frontiers in Psychology, 2022)
Teachers, as role models, are crucial in promoting inclusion in society through their actions. Being perceived as fair by their students is linked to students’ feelings of belonging in school. In addition, their decisions of resource allocations also affect students’ academic success. Both aspects underpin the importance of teachers’ views on justice. This article aims to investigate what teachers consider to be just and how teacher characteristics and situational factors affect justice ratings of hypothetical student-teacher-interactions. In an experimental design, we randomly varied the description of the interacting student in text vignettes regarding his/her special educational need (SEN) (situational factor). We also collected data on teachers’ attitudes toward inclusion and experiences with persons with disabilities (individual factors). A sample of in-service teachers in Germany (N = 2,254) rated randomized versions of two text vignettes. To also consider the effect of professional status, a sample of pre-service teachers (N = 275) did the same. Linear mixed effect models point to a negative effect of the SEN on justice ratings, meaning situations in which the interacting student is described with a SEN were rated less just compared to the control condition. As the interacting student in the situations was treated worse than the rest, this was indicative for the application of the need principle. Teachers with more positive attitudes toward inclusion rated the vignettes as significantly less just. Professional status also had a negative effect on justice ratings, with in-service teachers rating the interactions significantly lower than the pre-service teachers. Our results suggest that the teachers applied the principle of need in their ratings. Implications for inclusive teaching practices and future research are discussed further.